Germination physiology and autecology of Centaurea kilaea Boiss. from Turkey - Eskin, B.; Ozyigit, I.I.; Dogan, I.; Altay, V.; Demir, G.; Serin, M. (Universiti Kebangsaan Malaysia, 2013)
In this study germination requirements, plant-soil interactions and population biology of Centaurea kilaea was studied. The plant and soil samples were collected from Sofular Village (Şile District) and shore of Çatalca District (Istanbul) in Turkey by using standard methods. Methods like Scheibler, Wetdigestion, Kjeldahl and Olsen were employed for measurement of soil texture, structure and other physical and chemical characteristics (pH, total protein and electrical conductivity) using spectrophotometer, flame photometer, calcimeter and ICP. The results showed that ranges of different elements in the soil were 0.007-0.2% for N, 0.0007-0.001% for P, 0.001-0.01% for K, 0.0001-0.0002 % for Na. N, P, K and Na values in the plants were 2.17, 0.005, 0.1 and 0.006%, respectively. The data revealed that germination success of the seeds was influenced by the environmental factors such as pH, germination season and temperature.